Detailed analysis of the mRNAs mapping in the short unique region of herpes simplex virus type 1. - Rixon, F J (1985)
We have analysed the mRNAs which map within the short unique (US) region of the herpes simplex virus type 1 (HSV-1) genome. US has a total length of 12979 base pairs (1) and is extensively transcribed with approximately 94% of the total sequence present in cytoplasmic mRNAs and 79% of the total sequence considered to be protein coding. There are several examples of overlapping functions and multiple use of DNA sequence within this region. US contains 12 genes (1) which are expressed as 13 mRNAs. Two of these mRNAs are thought to arise from the same gene since they differ only slightly in the positions of their 5' ends and probably specify the same polypeptide. 11 of the 13 mRNAs are arranged into four nested families with unique 5' ends and common 3' co-termini. The other two mRNAs have unique 5' and 3' ends.